2001
DOI: 10.1063/1.1370949
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability of the clathrates Ba8Ga16Ge30, Sr8Ga16Ge30, Ba8Ga16Si30, and Ba8In16Sn30

Abstract: We use density functional calculations and single-crystal x-ray diffraction measurements to study structure and bonding in the solid state clathrates Ba 8 Ga 16 Ge 30 , Ba 8 Ga 16 Si 30 , Sr 8 Ga 16 Ge 30 , and Ba 8 In 16 Sn 30 . The structures calculated by minimizing the energy provided by the density functional theory agree well with those determined by x-ray scattering. The preferred stoichiometry is found to always have 8 group II, 16 group III, and 30 group IV elements. The resultant structures are shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
152
5
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(182 citation statements)
references
References 27 publications
24
152
5
1
Order By: Relevance
“…8 of the configurations are the same as considered in Ref. 31 Computed NMR lineshapes could be distinguished by the shapes of the noncentral portions of the lines, and we found that Al atoms situated in Al-Al pairs contributed the largest EFG's. For configurations with 3 or more Al-Al pairs this led to broad simulated lines providing poor agreement with the data.…”
Section: Computational Methods and Discussionmentioning
confidence: 63%
“…8 of the configurations are the same as considered in Ref. 31 Computed NMR lineshapes could be distinguished by the shapes of the noncentral portions of the lines, and we found that Al atoms situated in Al-Al pairs contributed the largest EFG's. For configurations with 3 or more Al-Al pairs this led to broad simulated lines providing poor agreement with the data.…”
Section: Computational Methods and Discussionmentioning
confidence: 63%
“…Blake et al 20 showed that the placement of the Ga atoms in the clathrate framework affects the stability of the compound. Since each substitutional Ga has one fewer valence electron than Ge or Si, the Ga concentration and its spatial correlation affect the energetics and the structure of the material.…”
Section: Clathrate Structurementioning
confidence: 99%
“…The details of the symmetries of each of these sites are described in detail in Ref. 20. For each calculation, we searched for a low total energy configuration by placing different numbers of the 16 Ga atoms on each symmetry site, by optimizing the geometry, and then by calculating the GGA total energy.…”
Section: A Ba 8 Ga 16 Ge 30 Compoundmentioning
confidence: 99%
“…The cage atoms are mostly from group 14 elements (Si, Ge, Sn) and/or group 13 (Al, Ga, In), but also transition metals and group 15 elements. On the other hand, the guest atoms are alkali metals (Na, K, Rb, Cs), [1][2][3][4] alkaline-earth or divalent rare-earth metals (Sr, Ba, Eu), [5][6][7][8][9] and halogens (Cl, Br, I) 10,11 which are loosely bound to the cage. Most of the compounds follow the Zintl rule, where the cage atoms are partially substituted by acceptor atoms for charge compensation between guest and cage.…”
Section: Introductionmentioning
confidence: 99%